2020
DOI: 10.1177/2382120520948879
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Writing Critical Thinking Reports as a Teaching Strategy on Today’s Hospital Wards

Abstract: I review some of the challenges in teaching medical students and housestaff on today’s hospital medicine wards, including increasingly limited time for dedicated teaching. Tapping into the extensive literature of “writing to learn” or “writing-across-the curriculum” in non-medical educational settings ranging from elementary school to college classes, I urge consideration of writing concise critical thinking reports (CTRs) by medical students and housestaff in response to questions raised during patient rounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The survey was conducted through posted online questionnaires (Qualtrics XM, Qualtrics, Provo, UT). Study questions were selected from a list of most viewed posts on P4P, an open-access noncommercial educational Web site dedicated to the practice of internal medicine 7,8 . P4P was created and launched in June 2015 by one of the authors (F.A.M.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was conducted through posted online questionnaires (Qualtrics XM, Qualtrics, Provo, UT). Study questions were selected from a list of most viewed posts on P4P, an open-access noncommercial educational Web site dedicated to the practice of internal medicine 7,8 . P4P was created and launched in June 2015 by one of the authors (F.A.M.…”
Section: Methodsmentioning
confidence: 99%
“…), an infectious diseases physician and an academic hospitalist, who also serves as the Web site’s administrator and editor on a voluntary basis. P4P aims to provide concise evidence-based answers to real-world clinical questions raised by internal medicine clinicians and medical students in the care of patients often generated during teaching rounds 7,8 . All of the posts are either authored or, when contributed by medical students, house staff, or other healthcare professionals, reviewed and modified as needed by the editor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the comprehensive curriculum of scientific competences in basic and clinical sciences, critical analysis adapted for technical writing has been inconsistently prioritised across health professions schools, especially in low- and middle-income countries. Limited information exists on the overall impact of collaborative writing activities for health professional students (Chen and Forbes, 2014; de Oliveira et al, 2011; Kusurkar, 2022; Manian, 2020). In addition, research training has been incorporated engaged with variably in medical schools, and the best pedagogical format or timeline for incorporating this content into established curricula is unknown (de Oliveira et al, 2011; Murray et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of writing to study or writing in the curriculum has been reported to positively impact learning in various educational settings, from elementary school to college classrooms. However, the results are mixed (Manian, 2020). Writing is a productive skill by using writing.…”
Section: Introductionmentioning
confidence: 99%